(untitled) (International Conference on Computers in Education, 2016)
Construction of models is promising as a learning activity. However, it can be a difficult activity which imposes heavy load on learners because it requires eminent Skills, This study proposes a basic framework for learning by constructing models of a production system in the domain of cognitive science. In this framework, a model abstractly describing human problem-solving processes and its computer model implemented on the production system is prepared by an instructor in advance. A learner is given the abstract model and problem-solving processes produced by executing the implementation model, and then engaged in instantiating the abstract model into an implementation model. This activity is expected to deepen learner understanding of cognitive processes embedded in the abstract model. We implemented a support system for the framework.